Resolva as expressões abaixo
A: (+6)÷(+2)=
B: (-10)÷(-2)=
C: (+8)÷(-2)=
D: (-15)÷(+3)=
E: (+30)×(+2)÷(-10)=
F: (-5)×(-2)÷(-2)=
G: (-50)÷(-2)×(+3)=
Soluções para a tarefa
Respondido por
0
Resposta:
A: 3
B: 5
C: -4
D: -5
E: -6
F: -1
G: 75
Espero ter te ajudado Bons estudos
Respondido por
0
Resposta:
a)3
b)5
c)-4
d)-5
e)-30
f)-5
g)75
Explicação passo-a-passo:
a)(+6)÷(+2)=3
b)(-10)÷(-2)=5
c)(+8)÷(-2)=-4
d)(-15)÷(+3)=-5
e)(+30)×(+2)÷(-2)=-30
f)(-5)×(-2)÷(-2)=-5
g)(-50)÷(-2)×(+3)=75
Perguntas interessantes
Matemática,
8 meses atrás
Matemática,
8 meses atrás
Contabilidade,
8 meses atrás
Química,
9 meses atrás
História,
1 ano atrás
Geografia,
1 ano atrás